LEGAL ASPECTS OF IMPLEMENTING THE KYOTO CONVENTION IN UZBEKISTAN’S CUSTOMS ACTIVITY AND IMPLICATIONS FOR WTO ACCESSION - Mukhiddinova, Dildora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the legal significance of the revised Kyoto Convention in the modernization of the customs procedures of Uzbekistan was analyzed. The issues of compliance of customs procedures with Convention standards, trade facilitation, efficiency, preservation of freedom, and a positive solution to the WTO membership process were discussed. The current customs legislation framework of Uzbekistan was reviewed, the necessary directions for compliance were determined, and the impact of implementation and WTO membership was studied. In the process of analysis, legal texts, international agreements, and literature were relied upon.